Histopathologic Findings Associated With Matrix Metalloproteinases Proceeding to Recurrence of Primary Spontaneous Pneumothorax in Adolescents - Chiu, Chih-Yung; Chen, Jim-Ray; Yin, Shun-Ying; Wang, Chia-Jung; Chen, Tzu-Ping; Hsieh, Tsan-Yu (Frontiers in Pediatrics, 2021)
Background: Primary spontaneous pneumothorax is potentially life-threatening, and its recurrence is always a serious problem. Pathological examination provides molecular insights into the pathophysiology of primary spontaneous pneumothorax. Objectives: To investigate the association of histopathologic features of primary spontaneous pneumothorax with matrix metalloproteinase expression and their relevance to the recurrence. Methods: A total of 217 tissue section slides in 172 adolescent patients with primary spontaneous pneumothorax were retrospectively reviewed from January 2001 to June 2020. All histopathologic features were recorded and pathologic findings related to ipsilateral recurrence and second surgery were analyzed. Serum levels of matrix metalloproteinases were prospectively measured in 25 primary spontaneous pneumothorax patients receiving surgery and 18 healthy controls. Their relevance to the histopathologic features of primary spontaneous pneumothorax related to its recurrence was also examined. Results: The major presenting histopathologic findings of primary spontaneous pneumothorax were bleb/bulla (98%) followed by fibrosis (68%). Low prevalence of the pathologic findings of granulation tissue and macrophage accumulation were significantly associated with recurrent primary spontaneous pneumothorax, whereas fibrosis was significantly higher in patients receiving more than once surgery. Furthermore, the ratios of matrix metalloproteinase-2/tissue inhibitor of metalloproteinase-1 and matrix metalloproteinase-9/tissue inhibitor of metalloproteinase-1 were significantly higher in theses pathological findings as well as multinucleated giant cells and mesothelial cell hyperplasia in comparison with healthy controls. Conclusions: Low prevalence of macrophage accumulation and granulation tissue related to the overexpression of matrix metalloproteinase-2 and -9 activities may contribute to healing impairment and primary spontaneous pneumothorax recurrence.